Efektifitas Konseling Kelompok Untuk Menurunkan Kecemasan Sebelum Melaksanakan Operasi Katarak - Purwantiningsih; Dewi Handayani; Meliana (NERSMID : Jurnal Keperawatan dan Kebidanan, 2019)
Anxiety is a natural disorder that is characterized by feelings of fear or anxiety that are deep and ongoing. Anxiety within normal limits is an inseparable part of human life. Anxiety in carrying out operations can be felt before, during and after the implementation of cataract operations. This anxiety is a combination of panic feelings with unpleasant physical sensations due to negative thoughts when going to cataract surgery. Meanwhile, one way to deal with nurse anxiety before performing cataract surgery is to use group counseling. This study aims to identify the effectiveness of group counseling in reducing nurses' anxiety before performing cataract surgery at Surabaya Undaan Eye Hospital. The populations of this study were all nurses working in surgery room Undaan Eye Hospital with 30 nurses and the sample selection were nurses who experienced anxiety before cataract surgery, 9 nurses. Primary data obtained through questionnaires distributed to the experimental group, namely nurses who experience anxiety. Furthermore, the experimental design chosen was a pretest posttest one group design, and then the analysis of the data used was Anova. The results showed the results of pretest parametric t-test 290.11 and mean posttest 182.78 results obtained t = 4.898 with p = 0.000 (p